Phonological Study of Onomatopoeia in Children’s Song - Nuri Ma'rifatil Laili; Fauzana Putri (Yayasan Visi Intan Permata, 2021)
This paper aims to observe the phonological features of onomatopoeia in children’s songs which contribute to foreign language acquisition. The study is a descriptive qualitative involving 24 full-time mothers who introduce English to their toddlers through various English songs. Data were collected through digital questionnaires followed up by semi-structured interviews to clarify what the parents had answered in the digital questionnaire. The study reveals numerous onomatopoeic words that acquired by the toddlers because of some factors, 1) the similarities of phonological features between English and Indonesian onomatopoeic words, and 2) the large quantities of language input in their listening habit.